2016
DOI: 10.18410/jebmh/2016/914
|View full text |Cite
|
Sign up to set email alerts
|

The GLN-Arg192 Polymorphism of Human Paraoxonase 1 Gene and the Associated Phenotype Variation Is Associated With Coronary Artery Disease in South-Indian Patients

Abstract: BACKGROUND Paraoxonase 1, an arylesterase, is associated with high-density lipoprotein and it prevents LDL from peroxidation by hydrolysing lipid peroxides and thereby providing protection against atherosclerosis. A polymorphism of paraoxonase 1 gene provoking a glutamine-to-arginine (A-allele or Q allele to B-allele or R allele) interchange at aminoacid-192 has been reported to determine differences in arylesterase activity towards LDL's oxidised aryl esters, hydrolysed at a higher rate by Q-alloenzyme than R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“…Whereas interestingly, the odds ratio of developing CAD were increased close to 2.706 -fold in the RR genotypes compared to healthy controls in Saudi populations. Our results were similar with recent findings of Saudi Arabian, North African and South Indian studies which also reported that CAD with RR genotype has more than 2 to 3 fold risk of developing coronary arthrosclerosis 10,17,26 .…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Whereas interestingly, the odds ratio of developing CAD were increased close to 2.706 -fold in the RR genotypes compared to healthy controls in Saudi populations. Our results were similar with recent findings of Saudi Arabian, North African and South Indian studies which also reported that CAD with RR genotype has more than 2 to 3 fold risk of developing coronary arthrosclerosis 10,17,26 .…”
Section: Discussionsupporting
confidence: 93%
“…The results of the Caerphilly study, the first potential epidemiological study of PON1 and CAD, also showed that activity of serum PON1 anticipate the coronary proceedings independent of all other coronary threat factors, as well as HDL 25 . Moreover, a recent study from Chandrasekaran S 2016 26 and Tan Y et al 27 supports the theory that lesser PON1 activity in the development of atherosclerosis. In contrast, in an Iranian 28 and Indian case-control studies 29 showed that no differences occur in PON1 activity in CAD patients and healthy individuals.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…Recently, dysfunctional, or proinfl ammatory HDL was indicated as a pro-atherogenic factor. Th e protective function of HDL against atherogenesis could be partly explained by its main constituent, PON1 [7].…”
Section: Introductionmentioning
confidence: 99%